The Thoughts of Sheikh Al Maududi and Ayatollah Baqir Shadr on Interest - Almer Ulul Albab; Sebastian Herman (Universitas Pembangunan Nasional Veteran Jakarta, 2023)
The past victories of Islam were weakened by stagnating scientific progress, slowing Muslim economic growth, and weakening military power in Islamic countries, and were easily defeated by the West. During this period, scholars were stigmatized as closed doors to Izhad and experienced a so-called sluggishness in which there was little development and innovation in both religion and science. Open the door to Ijtihad such as Johor ulema Dato' Syed Salim Abdullah al-Attas (1873-1899), Dato' Abdullah Musa (1899-1907), Syed 'Abd Qadir Muhsin al-Attas (1909 -1933) ) and Syed Alwi Tahir al-Haddad (1933-1941). Currently, Muslims are undergoing various attacks from scientific and economic aspects, especially in relation to interest, and until now, there are still some Muslims who do not consider interest, especially bank interest, to be haram. It's a pity. That's why scholars tried to empower Muslims, such as Sunni Abul Ala al-Moudi and Shia Sheikh Bakr Sadr. This study uses a literature review method with reference to selected journals and books and aims to explore whether there are differences between Sunnis and Shiites regarding this interest.